Usulan Rancangan Tata Letak Gudang PT. XYZ Menggunakan Metode ARC dan BLOCPLAN - Fitri Desti Cahyani; Tita Talitha (Program Studi Teknik Industri Universitas Setia Budi, 2026)
PT. XYZ is a manufacturing company engaged in the production of electronic devices such as smartphones, household appliances, and medical equipment. All finished products are stored in the main warehouse of the Logistics Department, which has a total area of 704.76 m². However, the current warehouse layout has not been systematically designed, leading to several operational problems. These issues include product accumulation, limited accessibility to certain items, disruption of internal transportation flow, and a high risk of product damage due to poorly organized storage paths. Random placement of goods without considering product characteristics, transfer volumes, and inter-activity relationships further exacerbates warehouse inefficiency. This study aims to propose a warehouse layout redesign using the Activity Relationship Chart (ARC) approach and the BLOCPLAN method. ARC is employed to map the proximity relationships between areas based on activity importance, while BLOCPLAN is applied to generate several efficient and realistic spatial layout alternatives. The analysis resulted in five alternative layouts with varying efficiency scores, with the best alternative achieving a score of 0.75. The proposed layout is considered more optimal in supporting material flow, accelerating internal distribution processes, and improving overall warehouse space utilization. Furthermore, the new layout supports the implementation of the First In First Out (FIFO) method, which is crucial for maintaining product quality and traceability.